Preparation of ceramic support coating using Tin (II) octoate: effect of Ethylene Glycol and Dimethyl Formamide solvent: article - Abd Jalil, Abdul Muiz; Suhaidi, Amira Nadzirah; Ibrahim, Norliza (2019)
Tin (II) Octoate usually used as catalyst in condensation polymerization in production of Polylactic acid (PLA). Problem comes as the phase of catalyst same as product and reactant which made catalyst difficult to be recycle and if this catalyst remain in product PLA plastic, the plastic quality will be affected. Experiment has been done to immobilize the Tin (II) Octoate in form of sol gel before coated on solid support which is ceramic. Parameters are chosen to determine the coating which are effect of Ethylene Glycol (EG) and Dimethyl Formamide (DMF) on the preparing the coating solution and this structure are characterized by Adhesion test and Field Emission Scanning Electron Microscopy Energy Dispersive X- ray (FESEM-EDX). The result showed that the coating layer that using Dimethyl Formamide (DMF) as a solvent contain about 36.96% tin (Sn) element which higher that the coating used Ethylene Glycol as solvent which only 11.43% content of tin (Sn) element. This showed that Dimethylformamide solvent is more efficient to be used as solvent and produce better coating characteristic in term of catalyst distribution and strength of catalyst attachment on ceramic support.